2021
DOI: 10.1016/j.ultsonch.2021.105542
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted hydration of finger millet (Eleusine Coracana) and its effects on starch isolates and antinutrients

Abstract: Highlights Ultrasound-assisted hydration process was developed and optimized for finger millet. Hydration was optimum at 65.73% amplitude, 26.13 min treatment and 1:3 grain-water ratio. Phytate and tannin (antinutrients) were reduced by 66.98 and 62.83%, respectively. Morphology, water binding capacity, and solubility of the isolated starch improved. The ultrasound-assisted hydration is a better alternative for finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 28 publications
1
40
0
8
Order By: Relevance
“…Guo et al (2015) obtained high phytate degradation (around 87%) using steam flash explosion pretreatment of wheat bran. An effective method to reduce the PA content of finger millet grain was demonstrated by Yadav et al (2021) who used a probe type ultrasound-assisted hydration (700 W, 20 kHz) with three different amplitudes (30, 50, 70%), treatment times (10, 20, 30 min) and different grain to water ratios. Mohammadi et al (2021) found that the proper combination of pH (2, 6, and 9) and ultrasonic treatment (28 kHz) was a successful method for dephytinization of rice bran.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2015) obtained high phytate degradation (around 87%) using steam flash explosion pretreatment of wheat bran. An effective method to reduce the PA content of finger millet grain was demonstrated by Yadav et al (2021) who used a probe type ultrasound-assisted hydration (700 W, 20 kHz) with three different amplitudes (30, 50, 70%), treatment times (10, 20, 30 min) and different grain to water ratios. Mohammadi et al (2021) found that the proper combination of pH (2, 6, and 9) and ultrasonic treatment (28 kHz) was a successful method for dephytinization of rice bran.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of linear polymeric chains in the amorphous region was broken by ultrasonic treatment. The packing arrangements of amylose–amylose and amylose–amylopectin could have increased the sample’s crystallinity if the arrangements were tighter [ 49 , 50 , 51 ]. The RC of starch complexing with resveratrol (Res-NS and Res-U 60 S) increased compared with the samples without resveratrol (NS and U 60 S, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…At higher ultrasound amplitude, heat is created in the sample, thus resulting in a rising temperature. The heat promotes the chemical deterioration of phytate to lower inositol phosphate, which helps in declining the phytate content of the sample (Yadav et al, 2021). Higher temperatures and increased treatment time normally cause higher solubility and degradation of polar organic compounds like oxalate.…”
Section: Reduction Of Oxalate Through Various Methodsmentioning
confidence: 99%